Melancholic Relationship to Appearance: A Fanonian Reading of Amadu’s Novel “No Past No Present No Future” - Abera Kassaw; Melakneh Mengistu (Richtmann Publishing, 2023)
This study is an exploration of the melancholic relationship to appearance reflected in Amadu Maddy’s “No Past No Present No Future”. To this end, the researcher uses textual analysis and descriptive criticism to unravel the causes and consequences of melancholic relationship to appearance. The theory of racial melancholia which is dominantly informed by Fanonian approach to the psychology of racism is used to account for the intra-psychic forces which operate within the melancholic characters in the subject novel. As the finding discloses, Amadu’s novel saw at close range that the immediate postcolonial world is dominated by two groups of people: some hermitized white souls whose mindset is stuck in more traditional forms of biological, and pseudo-scientific racism, and those black people with “black skin and white masks.”. Both exist in a borrowed time, unable to come to terms with the psychological states upon which their conscious and unconscious thoughts are hanging, have long lost wellness. The former see their articles of racial superiority as a self-evident truth; the latter plunge into a psychic process whereby the loss of belonging becomes the cause of ongoing trauma, realizing that they belong nowhere, that they must live in a world that would never give recognition to their existence. This study is an exploration of the melancholic relationship to appearance reflected in Amadu Maddy’s “No Past No Present No Future”. To this end, the researcher uses textual analysis and descriptive criticism to unravel the causes and consequences of melancholic relationship to appearance. The theory of racial melancholia which is dominantly informed by Fanonian approach to the psychology of racism is used to account for the intra-psychic forces which operate within the melancholic characters in the subject novel. As the finding discloses, Amadu’s novel saw at close range that the immediate postcolonial world is dominated by two groups of people: some hermitized white souls whose mindset is stuck in more traditional forms of biological, and pseudo-scientific racism, and those black people with “black skin and white masks.”. Both exist in a borrowed time, unable to come to terms with the psychological states upon which their conscious and unconscious thoughts are hanging, have long lost wellness. The former see their articles of racial superiority as a self-evident truth; the latter plunge into a psychic process whereby the loss of belonging becomes the cause of ongoing trauma, realizing that they belong nowhere, that they must live in a world that would never give recognition to their existence. Received: 03 October 2022 / Accepted: 30 December 2022 / Published: 5 January 2023